Effect of Development Coffee Beans Liberica Karawang, and Suistanable Economic Development with Business Incubation - Piantara, Seia (International Journal Accounting Tax and Business, 2024)
This study was carried out to help develop and utilize the agricultural potential of beans coffee Liberica plantations in Parungmulya Village, Ciampel District, Karawang City, both comparatively and competitively. This development is needed in accordance with developments that have been of interest and known to the general public, since 2018 the competitive forces in this research have been carried out based on developments that have been of interest and known to the general public since 2018, analyzing the competitive advantage of Indonesian coffee (Berlin Porter’s theory/Porter’s Diamond Theory). to look at the demand and supply sides of the market. The research results show that to increase national competitiveness, it is necessary to develop new entrepreneurs who are strong, creative, and professional. Business/entrepreneurial incubators are an effective vehicle for developing an entrepreneurial spirit, abilities, networks and business insight in accordance with Perpress No. 27 of 2013 concerning the Development of Entrepreneurial Incubators.